Halal awareness and Muslim consumer behavior in Indonesia: A systematic literature review - Deti, Sri (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2025)
This study presents a systematic literature review on halal awareness and consumption behavior of Muslim consumers in Indonesia, intending to synthesise empirical findings and identify key themes, theoretical contributions, and methodological gaps. Methodologically, this study confirms the relevance of thematic synthesis in Islamic marketing studies. A total of 42 indexed articles published between 2010–2024 were analysed using a thematic synthesis approach. The results of the study reveal four dominant themes: (1) halal awareness is understood as a multidimensional construct encompassing knowledge, attitude, and trust in halal authority; (2) halal consumption behavior is influenced by religiosity, awareness, socio-cultural factors, and demographic and psychographic characteristics; (3) local context, religious education, and community shape halal consumption practices; and (4) there are conceptual inconsistencies and a dominance of cross-sectional quantitative approaches. Theoretically, this study broadens the understanding of consumer behavior theory through the integration of Islamic values. Limitations include the period of publication and a limited database. Future research is recommended to develop comprehensive empirical models, longitudinal studies, mixed-method approaches and big data analysis. These findings are expected to be the basis for a more contextual and relevant halal marketing strategy.